2009
DOI: 10.4049/jimmunol.0801212
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Is Associated with a Down-Modulatory Lung Immune Response That Impairs Th1-Type Immunity

Abstract: Immune mediators associated with human tuberculosis (TB) remain poorly defined. This study quantified levels of lung immune mediator gene expression at the time of diagnosis and during anti-TB treatment using cells obtained by induced sputum. Upon comparison to patients with other infectious lung diseases and volunteers, active pulmonary TB cases expressed significantly higher levels of mediators that counteract Th1-type and innate immunity. Despite the concomitant heightened levels of Th1-type mediators, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 83 publications
8
118
1
1
Order By: Relevance
“…9,36 In addition to earlier reports that BAL fluids from a significant number of tested tuberculosis patients contained elevated IL-10 levels and bioactive TGF-b, 7 recent reports showed that lung cells from induced sputum expressed significantly high levels of IL-10, TGF-bRI and TGF-bRII. 37 In the present study, we found that the addition of anti-IL-10 or anti-TGF-b could partially reverse IFN-c production, suggesting that local IL-10 and TGF-b in PF may promote a cytokine microenvironment where resident and newly recruited immune cells become refractory to appropriate activating signals. …”
Section: Pf Inhibits the Functions Of T Cells And Differentiation Of supporting
confidence: 54%
“…9,36 In addition to earlier reports that BAL fluids from a significant number of tested tuberculosis patients contained elevated IL-10 levels and bioactive TGF-b, 7 recent reports showed that lung cells from induced sputum expressed significantly high levels of IL-10, TGF-bRI and TGF-bRII. 37 In the present study, we found that the addition of anti-IL-10 or anti-TGF-b could partially reverse IFN-c production, suggesting that local IL-10 and TGF-b in PF may promote a cytokine microenvironment where resident and newly recruited immune cells become refractory to appropriate activating signals. …”
Section: Pf Inhibits the Functions Of T Cells And Differentiation Of supporting
confidence: 54%
“…M. tuberculosis is known to promote down modulatory immune status and is shown to increase SOCS1 mRNA expression in patients with active TB as compared with patients with other infectious lung diseases or clinically healthy individuals [16]. Decrease in the levels of SOCS1 mRNA after chemotherapy in patients with TB suggests that M. tuberculosis alter the levels of these mediators to transit to active disease [16] A limitation of this study was that our identification of EC ESAT6 IFN-γ (+) as an M. tuberculosis exposed group is based on the measurement of IFN-γ responses only to ESAT6 and we were not able to classify our healthy subjects as having latent TB according to the commonly used commercial Quantiferon-TB Gold assay which measures an IFN-γ response to ESAT6, CFP10 and TB7.7 as the Quantiferon assay has not been available in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of SOCS1 may be one of the several mechanisms used by M. tuberculosis to antagonize immune activation of Th1 protective responses and facilitate survival of pathogen [16,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Ifnar1 2/2 mouse macrophages express lower levels of Socs1 during mycobacterial infection, and IFN-g-activated Socs1 2/2 macrophages have lower intracellular bacteria as a result of the increased IFN-g signaling (91). These experimental findings, together with the clinical observation that increased SOCS protein expression correlates with increased disease severity (92,93), hint that a detrimental role for type I IFNs in M. tuberculosis infection is to antagonize host-protective functions of IFN-g. TB is not the only mycobacterial disease associated with type I IFN induction. Self-healing tuberculoid leprosy is traditionally associated with the development of a Th1 response, whereas disseminated lepromatous leprosy is characterized by a Th2 response.…”
Section: Mycobacteriamentioning
confidence: 73%